The emerging role of exosome and microvesicle‐ (EMV‐) based cancer therapeutics and immunotherapy. Issue 3 (16th March 2017) - Moore, Colin; Kosgodage, Uchini; Lange, Sigrun; Inal, Jameel M.
Abstract : There is an urgent need to develop new combination therapies beyond existing surgery, radio‐ and chemo‐therapy, perhaps initially combining chemotherapy with the targeting specificities of immunotherapy. For this, strategies to limit inflammation and immunosuppression and evasion in the tumour microenvironment are also needed. To devise effective new immunotherapies we must first understand tumour immunology, including the roles of T cells, macrophages, myeloid suppressor cells and of exosomes and microvesicles (EMVs) in promoting angiogenesis, tumour growth, drug resistance and metastasis. One promising cancer immunotherapy discussed uses cationic liposomes carrying tumour RNA (RNA‐lipoplexes) to provoke a strong anti‐viral‐like (cytotoxic CD8 + ) anti‐tumour immune response. Mesenchymal stem cell‐derived EMVs, with their capacity to migrate towards inflammatory areas including solid tumours, have also been used. As tumour EMVs clearly exacerbate the tumour microenvironment, another therapy option could involve EMV removal. Affinity‐based methods to deplete EMVs, including an immunodepletion, antibody‐based affinity substrate, are therefore considered. Finally EMV and exosome‐mimetic nanovesicles (NVs) delivery of siRNA or chemotherapeutic drugs that target tumours using peptide ligands for cognate receptors on the tumour cells are discussed. We also touch upon the reversal of drug efflux in EMVs from cancer cells which can sensitize cells to chemotherapy. The use of immunotherapy in combination with the advent of EMVs provides potent therapies to various cancers. Abstract : What's new? This Mini‐Review brings together the field of exosomes and microvesicles (EMVs) as drug delivery vehicles together with the burgeoning area of cancer immunotherapy. We highlight the promise of cancer immunotherapies using exosomes and RNA lipoplexes as cancer vaccines, critically assess the promising but at times controversial results using Mesenchymal stem cell‐derived EMVs, discuss the possibility of therapeutic removal of EMVs and assess the use of EMVs and exosome‐mimetic nanovesicles (NVs) as drug delivery vehicles.